Simple and Efficient Transformation and Gene Editing of Marchantia polymorpha Spores - Yorker RM; Deroles SC; Zhou Y; Tate JA; Davies KM; Albert NW (Wiley Periodicals LLC, 2025)
Marchantia polymorpha (Marchantia) has become a model species for liverwort studies, owing to its rapid growth in vitro, ease of propagation, simple genetics, small genome, haploid-dominant life cycle, and because it is amenable to genetic transformation. Efficient transformation provides a foundation for many molecular and genetic analyses. The protocol described here is a simple and robust procedure for transforming Marchantia for a variety of applications, including gene overexpression and CRISPR genome editing. This simplified Agrobacterium tumefaciens-mediated transformation protocol targets spores, using common Agrobacterium strains GV3101 or EHA105, and overcomes challenges experienced in other methods. Spores are sterilized and distributed over sterile filter papers, which effectively retain spores and regenerating spores (known as sporelings). This approach enables the sporelings to be transferred to different agar growth media at different stages of transformation. A critical feature is preculturing the spores with acetosyringone (AS) prior to co-cultivation with Agrobacterium. This treatment profoundly enhances the transformation rate, particularly for Agrobacterium strain GV3101. GV3101 is preferred for its rapid growth rate, simple transformation, and lack of a recombinase (recA), stabilizing plasmids. The protocol is suitable for transforming Marchantia with constructs for CRISPR gene editing. Editing efficiency can be increased by introducing a heat-shock treatment during the transformation procedure, which increases the proportion of plants with larger edited sectors, facilitating mutant identification and propagation. Constructs and strategies for both overexpression and multiplex genome editing with sgRNA arrays using new and existing vectors are described. Using this spore transformation protocol for CRISPR gene editing, we routinely achieve 60% to 70% mutation rates, significantly reducing the effort required to generate and isolate mutants for functional analyses.
Keywords: Marchantia; liverwort; transformation; mutagenesis; CRISPR/Cas9